Antibiogram profiles and risk factors for multidrug resistance of Salmonella enterica recovered from Village Chickens (Gallus gallus domesticus Linnaeus) and other environmental sources in the Central and Southern Peninsular Malaysia - Jajere, Saleh Mohammed; Hassan, Latiffah; Zakaria, Zunita; Abu, Jalila; Abdul Aziz, Saleha (Multidisciplinary Digital Publishing Institute, 2020)
The emergence of multidrug resistance (MDR), including colistin resistance, among Enterobacteriaceae recovered from food animals poses a serious public health threat because of the potential transmission of these resistant variants to humans along the food chain. Village chickens or Ayam Kampung are free-range birds and are preferred by a growing number of consumers who consider these chickens to be organic and more wholesome. The current study investigates the antibiogram profiles of Salmonella isolates recovered from village chicken flocks in South-central Peninsular Malaysia. A total of 34 isolates belonging to eight serotypes isolated from village chickens were screened for resistance towards antimicrobials including colistin according to the WHO and OIE recommendations of critical antibiotics. S. Weltevreden accounted for 20.6% of total isolates, followed by serovars Typhimurium and Agona (17.6%). The majority of isolates (73.5%) demonstrated resistance to one or more antimicrobials. Eight isolates (23.5%) were resistant to ≥3 antimicrobial classes. Colistin resistance (minimum inhibitory concentrations: 4–16 mg/L) was detected among five isolates (14.7%), including S. Weltevreden, S. Albany, S. Typhimurium, and Salmonella spp. Univariable analysis of risk factors likely to influence the occurrence of MDR Salmonella revealed that the flock size, poultry production system, and use of antibiotics in the farm were not significantly (p > 0.05) associated with MDR Salmonella. The current study highlights that MDR Salmonella occur at a lower level in village chickens compared to that found in live commercial chickens. However, MDR remains a problem even among free-range chickens with minimal exposure to antibiotics.